Medical students’ attitude towards Psychiatry and Mental Disorders - Adhikari, SR (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: It is always difficult to attract medical students’ interest in Psychiatry as a career choice. Most of the students have negative views of Psychiatry even before entering medical school such as 1) stigma on patients and psychiatrists. 2) Unscientific specialty with less prestige. 3) Derogatory remarks by other specialty physicians. 4) Less financial return. This study was done to evaluate and analyze medical students’ attitude towards psychiatry at their different levels of medical career. Material and Method: Medical students from three different years were surveyed to assess their perception and attitude on psychiatry and related matters. First year students were surveyed when they joined within 2 weeks in medical college. Third year were given questionnaire at the first day of Psychiatry clerkship and 4th year students were also given on the first day of posting. Results: 280 students from 1st year (61 out of 100), 3rd year (79 out of 104) and 4th year (70 out of 76) studying MBBS were surveyed. Majority of students from different levels preferred medicine, surgery, pediatric when they first joined medical college and their current preference choice of specialization. Fifteen out of 61 first year students planned to join Psychiatry when they entered medical college which changed to 11 while they were enquired about current planning. Conclusion: Medical colleges need comprehensive course in Psychiatry that involves inpatient and outpatient to create interest in Psychiatry and we need strong advocacy to decrease stigma of “Psychiatry as a career choice” among medical students. J Psychiatrists’ Association of Nepal Vol .6(1), 2017, p.18-23